Prescription pattern among Iranian community dwelling older adults - Malihe Saboor; Yadollah Abolfathi Momtaz; Ahmad-Ali Akbari Kamrani; Robab Sahaf (Medicinski glasnik, 2018)
Aim: To assess prescription pattern among Iranian communitydwelling older adults. Methods: This cross-sectional study employed a cluster random sampling to obtain a sample of 1591 patients aged 60 years and over referred to pharmacies in Tehran, 2017. Data were collected using a questionnaire: socio-demographic characteristics, type of pharmacy visited, the municipal district, the university covering the pharmacy, the number and names of prescribed drugs, drug category, type of insurances and physician's socio-demographic profile (age, gender, type of specialization, and work experience). Results: The mean age of the patients was 70.51±7.84. A total of 5838 drugs were prescribed, giving an average of 3.73±2.24 drugs per patient (ranging of 1-15). Polypharmacy was noticed in 32.4% patients. Cardiovascular ‫‬ drugs accounted for 20.8% of the prescriptions, antidiabetics 8.8%, nutritional agents and vitamins 7.6%, and analgesics, anti-inflammatory drugs and antipyretics accounted for 7.5%. Conclusion: Developing educational programs on geriatric pharmacology general practitioners and more supervision among community-dwelling older adults might have effects on prescription pattern. There is a need for prescriber training and retraining with emphasis on the geriatric population.
Keywords: aged; general practitioners; medical specialists; prescription pattern